Chemical Composition and Bioactivity of a Carvacrol-Rich Thymus algeriensis Essential Oil from Gaser Alhaj, Libya - Abdulhamid A. Giweli; Omar T. Alzentani; Abdulwahab M. Kammon (Libyan Journal of Medical and Applied Sciences, 2025)
The genus Thymus is well-known for its aromatic and medicinal properties. Among its species, Thymus algeriensis is widely distributed in the Mediterranean basin, including Libya, where environmental conditions can influence essential oil composition and bioactivity. This study aimed to characterize the chemical profile of T. algeriensis essential oil collected from Gaser Alhaj and evaluate its antibacterial and allelopathic activities. Essential oil was extracted by hydrodistillation and analyzed using GC-MS, revealing six major compounds, with carvacrol as the dominant constituent (77.01%), followed by γ-terpinene, thymol, o-cymene, p-cymene, and caryophyllene. Oxygenated monoterpenes constituted the majority of the oil. The oil exhibited strong antibacterial activity against Escherichia coli and Salmonella gallinarum, and demonstrated dose-dependent allelopathic effects on Lactuca sativa seed germination. Compared to previous studies from Libya, this Gaser Alhaj oil represents a distinct carvacrol-rich chemotype with superior biological activity, highlighting regional chemotypic variation. These findings suggest that T. algeriensis essential oil has promising potential as a natural antimicrobial agent and eco-friendly bioherbicide.